Grape pomace and pecan shell fortified bread: The effect of dietary fiber-phenolic compounds interaction on the in vitro accessibility of phenolic compounds and in vitro glycemic index - Subiria-Cueto, Rodrigo; Olivas Armendariz, Imelda; Abraham, Wall-Medrano; de la Rosa, Laura A.; Martinez Ruiz, Nina Del Rocio; Alvarez-Parrilla, Emilio; Reyes-Blas, Hortensia; González-Aguilar, Gustavo A. (2024)
Grape pomace (GP) and pecan shell (PS) are two by-products rich in phenolic compounds (PC), and dietary fiber (DF) that may be considered for the development of functional baked foods. In this study, four formulations with different GP:PS ratios (F1(8%:5%), F2(5%:5%), F3(5%:2%), F4(0%:5%), and control bread (CB)) were elaborated and characterized (physiochemical and phytochemical content). Also, their inner structure (SEM), changes in their FTIR functional group’s vibrations, and the bioaccessibility of PC and sugars, including an in vitro glycemic index, were analyzed. Results showed that all GP:PS formulations had higher mineral, protein, DF (total, soluble, and insoluble), and PC content than CB. Additionally, PC and non-starch polysaccharides affected gluten and starch absorbance and pores distribution. In vitro digestion model showed a reduction in the glycemic index for all formulations, compared to CB. These findings highlight the possible health benefits of by-products and their interactions in baked goods.